DETERMINAN PROPORSI DANA TABARRU’ PADA LEMBAGA KEUANGAN ASURANSI UMUM SYARIAH - Puspitasari, Novi (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
Financial management in Islamic general insurance companies uses splitted fund system. Splitted fund system is a separation of assets and liabilities of tabarru’ and company funds group. Separation of the funds has been made since the participants pay the contribution (premium) at the beginning of the transaction. Contribution (premium) is separated into tabarru’ funds (funds for mutual help) and ujrah (fee for the operator/company). The purpose of this study is to test the determinant variables of tabarru’ fund proportion on Islamic general insurance company. The study was conducted on all Islamic general insurance companies, both full fledge Islamic system and business units. Purposive sampling method is used for determination of the sample. The period of the study was conducted from 2011 until 2013. This study used multiple regression analysis to answer the research problem. The results showed that claim, reinsurance activities, commission fees, and general and administrative expenses significantly affect the tabarru’ fund proportion.